Comparison of the Effectiveness of Cognitive-Behavioral Therapy and an Integrated Seven-Domain Competence-Based Approach in Reducing Suicidal Ideation Among Individuals Recovering from Substance Use Disorder - Samet , Mahdie Sadat; Mohammadipour, Mohammad; Bakhshipour, Abolfazl (KMAN Counseling & Psychology Nexus, 2026)
This study aimed to compare the effectiveness of cognitive-behavioral therapy and an integrated seven-domain competence-based counseling approach in reducing suicidal ideation among individuals recovering from substance use disorder. The study employed a single-case experimental design with repeated measures across twelve treatment sessions and an eight-week follow-up period. Six recovered individuals with substance use disorder were purposively selected from an addiction treatment center in Tehran Province and assigned to either a cognitive-behavioral therapy group or a seven-domain competence-based intervention group. Suicidal ideation was assessed at baseline, post-treatment, and follow-up using the Beck Scale for Suicide Ideation Questionnaire. Interventions were delivered weekly in forty-five-minute sessions. Data were analyzed through visual analysis and change-score comparisons to evaluate treatment effects and maintenance of gains. Both treatment approaches produced significant and clinically meaningful reductions in suicidal ideation. However, the seven-domain competence-based intervention resulted in significantly greater magnitude of improvement and superior maintenance of therapeutic gains at follow-up. Participants in this group demonstrated near-complete remission of suicidal ideation with minimal post-treatment relapse, whereas the cognitive-behavioral therapy group exhibited moderate symptom fluctuation and less stable long-term outcomes. The findings indicate that although cognitive-behavioral therapy is an effective intervention for reducing suicidal ideation among individuals in recovery from substance use disorder, an integrated seven-domain competence-based counseling approach may yield deeper and more durable psychological change.